2014
DOI: 10.1002/med.21329
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Cellular Nanomechanics in Cancer

Abstract: The biomechanical properties of cells and tissues may be instrumental in increasing our understanding of cellular behavior and cellular manifestations of diseases such as cancer. Nanomechanical properties can offer clinical translation of therapies beyond what are currently employed. Nanomechanical properties, often measured by nanoindentation methods using atomic force microscopy, may identify morphological variations, cellular binding forces, and surface adhesion behaviors that efficiently differentiate norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 121 publications
(157 reference statements)
0
30
0
Order By: Relevance
“…Recent experimental evidence [15][16][17][18] have revealed that tumor cells exhibit a broad distribution of various biomechanical properties. These include intra-tumor heterogeneity in cell stiffnesses [17,[19][20][21][22], stresses, and cell-cell interactions [21,23].…”
mentioning
confidence: 99%
“…Recent experimental evidence [15][16][17][18] have revealed that tumor cells exhibit a broad distribution of various biomechanical properties. These include intra-tumor heterogeneity in cell stiffnesses [17,[19][20][21][22], stresses, and cell-cell interactions [21,23].…”
mentioning
confidence: 99%
“…In particular, elastic modulus of tumors is an order of magnitude higher than elastic modulus of healthy tissues 23,24. Thus, tactile examination is a natural and efficient method for identification and localization of pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Atomic force microscopy (AFM) based single-cell force spectroscopy is an emerging method to directly investigate cellular mechanics and the dynamics of intercellular interactions (8,9). Excluding the immobilization of the melanoma cell, during these measurements there is no need for any staining or other cell-life impairing preparation.…”
Section: Introductionmentioning
confidence: 99%